2020
DOI: 10.1051/ro/2019111
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on path factors in graphs

Abstract: A spanning subgraph of a graph is defined as a path factor of the graph if its component are paths. A $P_{\geq n}$-factor means a path factor with each component having at least $n$ vertices. A graph $G$ is defined as a $(P_{\geq n},m)$-factor deleted graph if $G-E'$ has a $P_{\geq n}$-factor for every $E'\subseteq E(G)$ with $|E'|=m$. A graph $G$ is defined as a $(P_{\geq n},k)$-factor critical graph if after deleting any $k$ vertices of $G$ the remaining graph of $G$ admits a $P_{\geq n}$-factor. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…A graph Gnbsp1emκ(G)2m+1 and bind(G)>3m+12m+1 is a (P3,m)‐factor deleted graph, where mdouble-struckN. The bound of binding number improves the given theorem in Zhou 17 …”
Section: Conclusion and Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…A graph Gnbsp1emκ(G)2m+1 and bind(G)>3m+12m+1 is a (P3,m)‐factor deleted graph, where mdouble-struckN. The bound of binding number improves the given theorem in Zhou 17 …”
Section: Conclusion and Discussionsupporting
confidence: 51%
“… Zhou et al 22 proved that a graph G with κ(G)k+2 is a (P3,k)‐factor critical graph if t(G)k+12, and the counterexample in this paper implies that t(G)k+12 and κ(G)k+2 here cannot be replaced by t(G)k+13 and κ(G)k+1. However, the bound of toughness is not tight, and it may find a better toughness bound between k+12 and k+13. Zhou 17 determined that a graph G is a (P3,m)‐factor deleted graph if κ(G)2m+1 and bind(G)6m+54m+4 where m is a nonnegative number, and the example provided by author showed that the bounds cannot be reduced to κ(G)2m and bind(G)6m+54m+5. Although κ(G) bound is tight, this example cannot interpret the binding number bound is sharp.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Zhou, Yang and Xu [22] proved that an n-connected graph G is (P ≥3 , n)-factor critical if its toughness tough(G) ≥ n+1 2 . Some other results on path factors can be found in [3,15,17,18]. Lots of authors derived some toughness conditions for the existence of graph factors [4,5,9,20].…”
Section: Introductionmentioning
confidence: 99%